Regulative Conditions of Existence of Doppler Effect Using Green Function Formalism - El-Bahi, R (The International Journal of Multiphysics, 2017)
The Doppler shift of the near and far Waves due to the electromagnetic source in motion is investigated. Using the decomposition of Green’s function for the wave in the case of classical oscillating electron motion, it is found that there are some regulative conditions of the phenomena. The present theory proves that the shift is undefined in the adjacent area. Actually, the spectrum of the radiation field in the adjacent area is ambiguous. The current theory establishes a regular Doppler effect in the distant area. Bearing in mind that the propagator coupled with the electric field takes a shifted frequency. Once, the relationship between the far-field frequency, the oscillating dynamic source have been established, the spectrum exists and can be analyzed.